High stakes testing : coping with collateral damage - Thomas, R. Murray (Robert Murray), 1921-2016 (L. Erlbaum Associates, 2005)
The US No Child Left Behind Act put high-stakes testing into the educational limelight. The purpose of this book is to: describe high-stakes testing; identify types of collateral damage that have attended the testing programs; analyze methods for coping with the damage; and suggest lessons to be learned from the high-stakes-testing experience.